Supplementation of Freezing Medium with Alpha-Mangostin Improves Human Sperm Quality after Cryopreservation - Kokmas, Wanlapa; Kruevaisayawan, Hathairat; Amatyakul, Patcharada; Khongsombat, Onrawee (Journal of Basic and Applied Pharmacology, 2018)
Sperm cryopreservation, a routine technique in assisted reproductive technology (ART), is an efficient procedure to preserve sperm viability. Even though cryo-preservation has benefits on fertility preservation, it has a negative effect on sperm due to oxidative stress, causing damage and affecting sperm quality. The addition of antioxidants to the freezing media may protect the sperm quality after cryopreservation. Alpha-mangostin (α-MG) has been confirmed as having high potential antioxidant effects in several cell types. However, the protective effect of α-MG on sperm quality after cryopreservation has not yet been explored. This study aimed to investigate the effect of α-MG supplementation to a freezing media on motility, viability, malondialdehyde (MDA) level and catalase (CAT) activity in human sperm. Semen samples were obtained from 7 healthy men and divided into following groups (n=7 per group): control, freezing medium supplemented with 25 and 50 µM α-MG. Sperm samples were frozen by vitrification technique and stored at -196°C. After 2 weeks, the sperm samples were thawed and all parameters were evaluated. The results showed that supplementation with 25 and 50 µM α-MG in the freezing medium tended to increase the total sperm motility and progressive sperm motility. Furthermore, supplementation with 50 µM α-MG significantly increased sperm viability, CAT activity and decreased MDA level (p<0.05). Alpha-mangostin contains an antioxidant effect that could scavenge the reactive oxygen species (ROS) thus achieving a balance between ROS and the antioxidant activity. Therefore, α-MG may protect human sperm damage from cryopreservation.